The transcription factor Grainy head and the steroid hormone ecdysone cooperate during differentiation of the skin of Drosophila melanogaster - Gangishetti, Umesh; Lohmann, Ingrid (Insect molecular biology, 2012)
The arthropod epidermis is an epithelium that deposits the apical cuticle, which is a stratified extracellular matrix (ECM) protecting the animal against pathogens, preventing dehydration and also serving as an exoskeleton. Differentiation of the cuticle conceivably implies coordinated production, secretion and localization of its components. The underlying molecular mechanisms are poorly explored. In this work, we show that the transcription factor Grainy head and the steroid hormone ecdysone drive the production of two partially overlapping sets of cuticle factors. Nevertheless, Grainy head is needed to modulate the expression of ecdysone signalling factors; the significance of this cross-talk is yet unclear. In addition, we found that ecdysone signalling negatively regulates its own impact. In conclusion, our findings suggest that at least two independently triggered pathways have evolved in parallel to cooperatively ensure the stereotypic implementation of the cuticle. As Grainy head is also essential for epithelial differentiation in vertebrates, we speculate that it acts to decode the ancient skin programme common to all animals. Full differentiation of the skin necessitates a second, complementing taxon-specific programme that requires its own decoder, which is represented by ecdysone in arthropods, whereas the vertebrate specific one remains to be identified.